SATIRICAL HUMOR AS CRITICS OF GOVERNMENT THROUGH EASTERN INDONESIAN STAND-UP COMEDIAN - Lambok Hermanto Sihombing (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2022)
In Indonesia, Stand-up Comedy has become the most popular form of community entertainment, resulting in the emergence of influential youth culture. Stand-up Comedy has become a platform for comics to communicate political aspirations, worries, and criticisms. Three comics from Eastern Indonesia, Arie Kriting, Abdur, and Mamat Alkatiri, have continuously presented Stand-up Comedy material regarding socioeconomic disparity and the availability of public services in their native region. In addition to the aforementioned concerns, education, emancipation, economic, and technological issues are common discussion topics. Typically, Eastern Indonesian comic elements communicate criticisms and worries about inequality and underdevelopment. Due to the presence of some Comics from East Indonesia who regularly expressed and voiced the unrest and backwardness felt by the people of East Indonesia, this issue became popular and garnered widespread attention. This qualitative study analyzes the utilization of satire in stand-up comedy content. This study utilized Barbara Swovelin (2019) concept of Horatian Satire, Friedman's Menippean Satire (2019), and Van Dijk's Critical Discourse Analysis approach. As a result of this study, Eastern comics used sarcasm and humorto express their dissatisfaction with the government.